(Table T1) Calcium carbonate content of ODP Hole 181-1121B, southwest Pacific - Haidi JL Hancock; Gerald Roy Dickens (PANGAEA, 2002)
Site 1121 is located southeast of New Zealand on the Campbell Drift (50°53.876 extquotesingleS 176°59.862 extquotesingleE) at a water depth of 4487.90 meters below sea level (mbsl). The site was drilled to recover an expanded sediment sequence from a Neogene contourite drift (Shipboard Scientific Party, 1999, doi:10.2973/odp.proc.ir.181.105.2000). Unexpectedly, the sequence between 32.7 and 132 meters below seafloor (mbsf) is composed of Paleogene siliceous and nannofossil-bearing ooze and chalk (Shipboard Scientific Party, 1999, doi:10.2973/odp.proc.ir.181.105.2000). This finding is intriguing because the location was probably fairly deep (>3800 mbsl) during the Paleogene (Shipboard Scientific Party, 1999, doi:10.2973/odp.proc.ir.181.105.2000), suggesting a carbonate compensation depth (CCD) significantly lower than expected from Cenozoic CCD curves (van Andel, 1975, doi:10.1016/0012-821X(75)90086-2). Therefore, 39 samples of sediment were taken from Hole 1121B to construct a more detailed carbonate record of this interesting lithologic unit.
Supplement to: Hancock, HJL; Dickens, GR (2002): Data report: Carbonate concentrations of paleogene sediment at Hole 1121B, Campbell Drift. In: Richter, C (ed.) Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 181, 1-5, https://doi.org/10.2973/odp.proc.sr.181.204.2002